(untitled) (BIRDEM Medical Journal, 2020)
Background: There are variable effects of Ramadan fasting on clinical and biochemical variables of diabetic people. Anti-diabetic agents are often adjusted during this time to reflect changes in lifestyle. The study was conducted to understand the diversity of follow-up, treatment pattern, clinical, and biochemical outcome of Ramadan fasting among type 2 diabetic patients who observed Ramadan fast. Methods: This real-world, multi-center, prospective, observational study was conducted at the diabetes outpatient department of National Healthcare Network (NHN) Uttara Center of Bangladesh Diabetic Somity (BADAS), Dhaka, Bangladesh and outpatient department of MARKS Hormone and Diabetes clinic, MARKS Medical College &Hospital in Dhaka, Bangladesh upon randomly selected type 2 diabetic patients, recruited 1 to 12 weeks prior to the Ramadan and followed up till 12 weeks post-Ramadan period. Finally, a total of 271 participants completed satisfactory follow up. Data was collected before, during, and after Ramadan using a set of questionnaires in a face to face interview. Results: The majority (80.1%) of participants received pre-Ramadan education, counseling, adjustment of medication and other direction to help them cope with Ramadan fasting. A significant reduction of weight, body mass index (BMI)) and blood pressure were reported after Ramadan fast (p<0.001). None of the studied participants experienced severe hyper/hypoglycemia or acute complications requiring hospitalization or an emergency room visit. Metformin was the commonest prescribed anti-diabetic medication. Premixed insulin was the commonest insulin regimen during study period. Three most commonly adjusted oral anti-diabetic drugs were gliclazide, glimepiride, metformin and insulin doses were also adjusted. Mean of fasting and prandial capillary blood glucose decreased from pre-Ramadan period to post-Ramadan period (P<0.05). HbA1c decreased during post-Ramadan period compared to pre-Ramadan visit (P=0.13). A significant reduction in the triglyceride level was observed during post-Ramadan follow up (P< 0.05). Conclusion: The study revealed that a safe fasting can be observed with proper pre-Ramadan work-up. Ramadan fasting resulted into significant reduction of weight, BMI, blood pressure, lipid profile and improved glycemic status in patients with type 2 diabetes. Birdem Med J 2021; 11(1): 30-38